Analisis Perbandingan Rasio Profitabilitas dan Non Performing Loan (NPL) pada Kinerja Keuangan Bank Umum Konvensional dan Bank Umum Syariah - Eka Rimba (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
This study aims to analyze the comparison of financial performance between conventional commercial banks and sharia commercial banks in Indonesia. This research is a type of descriptive research with a quantitative approach. The population taken in this study are commercial banks registered with the Otoritas Jasa Keuangan (OJK). Sampling in this study was conducted using purposive sampling technique so that a sample of 11 conventional commercial banks and 9 sharia commercial banks was obtained. The data used is secondary data obtained from the published annual reports of each commercial bank registered with the Otoritas Jasa Keuangan (OJK) during the 2016-2020 period. The data in this study consists of financial ratios Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin/Net Operating Margin (NIM/NOM), Operating Costs to Operating Income (BOPO), and Non-Performing Loans/Non-Performing Financing (NPL/NPF). In this study, data analysis was carried out using descriptive statistical analysis and the two-sample independent test of non-parametric statistics, namely the Mann Whitney test. After analyzing the data, the results show that there are differences in the financial performance of conventional commercial banks and sharia commercial banks as measured by the ratio of ROA, ROE, NIM/NOM, BOPO and NPL/NPF. In general, the financial performance of conventional commercial banks is better than that of Islamic commercial banks.